Improvement and Performance Evaluation of GPSR-Based Routing Techniques for Vehicular Ad Hoc Networks - Andrey Silva (IEEE Access, 2019)
Geographic routing has been widely studied over the years as an effective solution for Vehicular Ad Hoc Networks (VANETs), especially because of the availability of wireless devices and global positioning system services. Given the unpredictable behavior of VANETs, selecting the next relay node has been proved a very challenging task. Therefore, in order to maintain acceptable network performance, the routing algorithm needs to be carefully designed to adapt to the fast network changes. The Geographic Perimeter Stateless Routing (GPSR) protocol is a widely adopted position-based routing protocol for VANETs, which makes it a good benchmark candidate. In this paper, we analyze the shortcomings of GPSR and propose a new strategy named Path Aware GPSR (PA-GPSR), which includes additional extension tables in the Neighbors' Table to select the best path and bypass the nodes that have delivered such previous packets in recovery mode. Moreover, our proposed algorithm can eliminate packet routing loops avoiding the delivery of the same packet to the same neighbor node. These PA-GPSR features can, for instance, help to overcome link-breakage due to the unavoidable reasons, such as road accidents or dead-end roads. We used the Simulation of Urban MObility (SUMO) and Network Simulator-version 3 (NS-3) platform to compare our proposed algorithm to the traditional GPSR and Maxduration-Minangle GPSR (MM-GPSR) in scenarios varying the number of nodes as well as the number of source-destination pairs. Our results show that the proposed PA-GPSR strategy performed better than the traditional GPSR and MM-GPSR when packet loss rate, end-to-end delay, and network yield are considered as performance metrics.